Health manpower survey, 1965 : hospitals and clinics, dispensaries and maternity centres, health centres, health offices and specialist units - Federal Ministry of Economic Development (Lagos : National Power Board, Federal Ministry of Economic Development, 1969)
The main objective of the survey was to obtain information on the total employment position in the various types of health institutions broken down by region, nationality and sex, and to collect data on the numbers of health institutions in the country, their distribution over the Federation, and their dates of establishment, the object of the latter being to facilitate the illustration of their growth over the years. The survey also sought data on the degree of utilization of health institutions for training certain categories of health manpower.
rpm 21/02/2018
Ref.
Keywords: Medical personnel